Impact of Hyperspeed Iron Microparticles on Light Transmission of Quartz Glasses with Protective In-Sn-O Coating in the Ultraviolet Range; Russian Physics Journal; Vol. 67, iss. 6 - Tursunkhanova R. Ryskul; Sergeev V. P. Viktor Petrovich; Sergeev O. V.; Neufeld V. V.; Khristenko Yu. F. (2024, 2024)
Title screen